Analyzing the Interplay of Technology Adoption, Farmer Training, Market Access, and Crop Yield: A Quantitative Survey in Agribusiness - Rusmayadi, Gusti; Salawati, Umi; Widi, Riantin Hikmah; Suparwata, Dewa Oka (International Journal of Business, Law, and Education, 2024)
This research delves into the intricate interplay of Technology Adoption (TA), Farmer Training (FT), Market Access (MA), and Crop Yield (CY) within the contemporary agribusiness landscape. With the global population burgeoning and climate change reshaping traditional paradigms, the need to enhance agricultural efficiency and resilience is paramount. Through a quantitative survey and Partial Least Squares Structural Equation Modeling (PLS SEM) analysis, the study explores the relationships among these pivotal factors. The findings underscore the significant impact of technology adoption, farmer training, and market access on crop yield, supported by established theories. The diverse respondent demographic, methodological rigor, and hypothesis testing further fortify the study's credibility. This research not only contributes to academic knowledge but also provides practical insights for policymakers and industry stakeholders, fostering a harmonious integration of key elements to enhance agribusiness sustainability.